PEMBERIAN LIMBAH DIAPERS DAN PUPUK KOTORAN KAMBING TERHADAP JUMLAH DANLEBAR DAUN KANGKUNG DARAT (Ipomoea reptans Poir) - Tri Fazhilah; Atip Nurwahyunani, Lussana Rossita Dewi, Fibria Kaswinarni (Jurnal Salome : Multidisipliner Keilmuan, 2023)
This study aims to determine the effect of applying diapers and goat manure on the growth of groundwater spinach (Ipomoea reptans Poir). This research was conducted on agricultural land Jl. Kyai Banjaran KM 09 Bedali hamlet, Kuripan village, Watumalang sub-district, Wonosobo district in November 2022-January 2023. The study used an experimental method with a non- factorial Completely Randomized Design (CRD) with 6 treatments and 3 replications. The treatments tried were as follows: A0 = Control/100% soil, A1 = 100% goat manure, A2 = 25% diapers + 75% goat manure, A3 = 50% diapers + 50% goat manure, A4 = 75% diapers waste + 25% goat manure, and A5 = 100% diapers waste. The parameters observed in this study included the number of leaves and leaf width which were analyzed using SPSS 22 with One Way ANOVA and DMRT follow-up test. The results showed that there was a significant effect of giving diapers and goat manure on the growth of groundwater spinach (Ipomoea reptans Poir). Treatment A1 (100% goat manure) showed the highest yield on the number of leaves (6.6667b), and treatment A3 (50% waste diapers + 50% goat manure) showed the highest yield on leaf width (5.8000c).